Projective Mapping & Sorting Tasks - Valentin, Dominique; Chollet, Sylvie; Nestrud, Michael; Abdi, Hervé (Descriptive Analysis in Sensory Evaluation, 2018)
Projective mapping and sorting tasks—often called “Holistic” Methods—are methods that directly obtain similarity measurements between products by asking participants (who could be novices, trained assessors, or experts, adults or children) to provide a global evaluation of a set of products of interest. In projective mapping, each participant is asked to place products on a sheet of paper in such a way that the positions of the products express the products’ similarity structure. In the sorting task, each participant is asked to sort the products in groups such that similar products are sorted together. For both projective mapping and sorting—in order to derive a better understanding of the similarity structure between the products—participants are also sometimes asked to verbally describe products or groups of products. The statistical analysis of projective mapping and sorting tasks used well know techniques such as: (multiple and simple) correspondence analysis, multiple factor analysis, principal component analysis, multidimensional scaling, and DISTATIS.